2018
DOI: 10.1021/acs.macromol.8b01946
|View full text |Cite
|
Sign up to set email alerts
|

Side-Chain Sequence Enabled Regioisomeric Acceptors for Conjugated Polymers

Abstract: Side-chain sequence enabled regioisomeric acceptors, bearing different side-chain sequences on the same conjugated backbone, are herein reported. Two regioregular polymers PTBI-1 and PTBI-2 and one regiorandom polymer PTBI-3 were synthesized from these two regioisomeric acceptors for a comparative study. UV–vis–NIR absorption spectroscopy and electrochemical study confirmed similar frontier molecular orbital levels of the three polymers in their solid state. More intriguingly, absorption profiles suggest that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 45 publications
0
16
0
Order By: Relevance
“…Mei and co‐workers reported on P112 , P113, and P114 , in which both the linear and branching alkyl chains are attached to the backbones . They found that the sequence of the arrangement of alkyl chains along the backbone has a significant effect on the aggregation behaviors of polymer chains.…”
Section: Alkyl Chains With Different Structuresmentioning
confidence: 99%
“…Mei and co‐workers reported on P112 , P113, and P114 , in which both the linear and branching alkyl chains are attached to the backbones . They found that the sequence of the arrangement of alkyl chains along the backbone has a significant effect on the aggregation behaviors of polymer chains.…”
Section: Alkyl Chains With Different Structuresmentioning
confidence: 99%
“…[ 29 ] Isoindigo unit can also be replaced by only a thienyl ring to obtain an asymmetric derivative thieno‐benzo‐isoindigo ( M2 ). [ 44,89–91 ] However, M2 ‐based P15 exhibited low OFET performance even though the coplanarity of M2 was much higher than that of isoindigo, due to the face‐on polymer orientation. [ 44 ]…”
Section: Modification Strategies Of Isoindigo‐derived Polymer For Ofetsmentioning
confidence: 99%
“…[29] Isoindigo unit can also be replaced by only a thienyl ring to obtain an asymmetric derivative thieno-benzo-isoindigo (M2). [44,[89][90][91] However, M2-based P15 exhibited low OFET performance even though the coplanarity of M2 was much higher than that of isoindigo, due to the face-on polymer orientation. [44] The electron-rich thiophene ring elevates the LUMO energy level of M1, which is not conducive to achieve ambipolar transport.…”
Section: Replacing the Benzene Rings In Isoindigo Unit With Heterocyclesmentioning
confidence: 99%
“…Subsequently, they reported a thiophene‐based monomer, bis‐thienobenzo‐IID (bis‐TBI), by coupling two benzothieno‐IID moieties together at the thienyl position and synthesized a copolymer (P46) of bis‐TBI and bithiophene moieties. [ 135 ] The HOMO/LUMO energy level of P46 was −5.43/−4.01 eV. GIXRD results indicated that P46 adopted both edge‐on and face‐on orientations, and the π–π stacking distance was very small (3.51 Å).…”
Section: Improving the Electron Transport Of D–a‐type Sps Via Amsmentioning
confidence: 99%
“…c) AFM height images and GIWAXS patterns of the polymer film prepared by bar coating (perpendicular). Reproduced with permission [135]. Copyright 2019, Wiley-VCH.…”
mentioning
confidence: 99%